No girls allowed (dogs okay) - Trueit, Trudi Strain (Secrets of a lab rat, 2009)
Fearless nine-year-old "Scab" McNally tries to get his twin sister's help in convincing their parents to let them get a dog, but when he embarrasses her in school with a particularly obnoxious invention, it looks like he has lost her cooperation forever.